1993
DOI: 10.4049/jimmunol.150.9.3951
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to Toxoplasma gondii major surface protein (SAG-1, P30) inhibit infection of host cells and are produced in murine intestine after peroral infection.

Abstract: Monoclonal and polyclonal, monospecific antibodies to the major surface antigen of Toxoplasma gondii (SAG-1, P30) inhibit infection of human fibroblasts and murine enterocytes. Fab prepared from polyclonal, monospecific antibody to P30 also have this inhibitory effect on invasion, which indicates that this antibody directly blocks parasite infection of host cells rather agglutinating the parasite. Antibodies to another surface protein (P22) did not alter in vitro infection. If the inhibitory effect of antibody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…None of our assays has revealed a functional difference between p25 and p28 Sko parasites; this implies that the encoded proteins are redundant. Interestingly, functional redundancy has been described for the various GPI‐anchored, cysteine‐rich surface proteins of the SAG multigene family in the related apicomplexan parasite T.gondii (Mineo et al ., 1993). Like P25 and P28, antibodies to SAG1 inhibited parasite interaction with host tissues, yet SAG1 ‐deficient parasites were invasive, as were SAG3 ‐negative parasites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…None of our assays has revealed a functional difference between p25 and p28 Sko parasites; this implies that the encoded proteins are redundant. Interestingly, functional redundancy has been described for the various GPI‐anchored, cysteine‐rich surface proteins of the SAG multigene family in the related apicomplexan parasite T.gondii (Mineo et al ., 1993). Like P25 and P28, antibodies to SAG1 inhibited parasite interaction with host tissues, yet SAG1 ‐deficient parasites were invasive, as were SAG3 ‐negative parasites.…”
Section: Discussionmentioning
confidence: 99%
“…Anopheles gambiae was used because in this species innate immune responses have been de®ned which can be used as markers for the process of crossing the epithelium by P.berghei ookinetes (Dimopoulos et al, 1997(Dimopoulos et al, , 1998. In addition, a refractory strain of A.gambiae encapsulates and melanizes ookinetes in the BL region of the epithelium after crossing the epithelium and as they emerge into the extracellular space (Paskewitz et al, 1988). Unlike normal ookinetes, these melanized ookinetes can easily be detected.…”
Section: Ookinetes Lacking P25 and P28 Can Traverse The Midgut Epithe...mentioning
confidence: 99%
“…The T. gondii surface protein SAG1 is taken up through endocytosis in extracellular tachyzoites 31 so we targeted this molecule to develop a new endocytosis assay for parasites within the host cell vacuole. Previous assays for endocytosis of SAG1 in extracellular parasites used antibodies targeting SAG1 31 but these antibodies are known to also inhibit invasion 49 and, therefore, are incompatible with the analysis of intracellular parasites. Instead, we modified the sag1 gene to express a fused HaloTag that can catalyze covalent linkage to exogenous fluorescent ligands 50 .…”
Section: Resultsmentioning
confidence: 99%
“…Several pieces of evidence support the association of antibodies in the defense against pathogens using diverse methods, such as inhibiting the attachment to host cells [ 48 ]. Much of the literatures has shown that Toxoplasma -specific antibodies can block the in vitro penetration of enterocytes by tachyzoites [ 49 , 50 , 51 ]. Thereby, in the current study, the capability of the harvested sera from mice two weeks following the completion of different immunization regimens to prevent in vitro parasite invasion was assessed.…”
Section: Discussionmentioning
confidence: 99%